Anion exchange resin as well as preparation method and application thereof

By using anion exchange resins prepared by using acrylamide, methacryloyloxyethyltrimethylammonium chloride and other materials, the problem of removing dichromate ions in aqueous solution is solved, and efficient removal and reuse of resin are achieved, while enhancing the The compressive strength of the resin is eliminated, and the crushing problem during separation is avoided.

CN119119355AInactive Publication Date: 2024-12-13SOUTHWEST PETROLEUM UNIV

Patent Information

Application Number
CN202411351631.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove dichromate ions in aqueous solution, and the compressive strength of the resin is insufficient after removal, resulting in possible fragmentation during separation.

Method used

Using anion exchange resin composed of acrylamide, methacryloyloxyethyltrimethylammonium chloride, potassium persulfate and N,N-methylenebisacrylamide, the monomer, initiator and crosslinking agent are synthesized. A combination of the resins with high removal rate and reuse capability were prepared.

Benefits of technology

The efficient removal rate of dichromate ions in aqueous solution (94.21%) and the reusable performance of resin are achieved. The resin has sufficient compressive strength after adsorption to avoid crushing and maintain a good removal effect within the pH 2-10 range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119355A_ABST
    Figure CN119119355A_ABST
Patent Text Reader

Abstract

The invention discloses anion exchange resin. Raw materials comprise a synthetic monomer, an initiator and a cross-linking agent, wherein the synthetic monomer comprises methacryloyloxyethyl trimethyl ammonium chloride and acrylamide according to the weight ratio of 7: 3; the initiator comprises potassium persulfate and acrylamide in a weight ratio of 1: 20; the cross-linking agent comprises N, N-methylene bisacrylamide and acrylamide according to the weight ratio of 1: 20. Methacryloyloxyethyl trimethyl ammonium chloride is introduced into a polyacrylamide resin polymerization system, so that the water-absorbent resin has a quaternary ammonium salt-N (CH3) < 3 + > functional group, and dichromate ions in an aqueous solution can be removed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and more particularly to an anion exchange resin and a preparation method and application thereof. Background Art

[0002] Cr(VI) is a carcinogen with potential risks of carcinogenesis, teratogenesis and mutagenesis. It can easily affect the cells themselves or cause mutations, and can easily induce cancer in organs such as the lungs, liver and kidneys. Cr(VI) also has adverse effects on plants. When plants ingest Cr(VI), nutrient absorption is reduced, photosynthesis efficiency is reduced, growth is slowed down, and in severe cases, yellowing and necrosis can occur.

[0003] The sources of Cr(VI) pollution in the environment are wide-ranging and can be mainly divided into two categories. One is natural sources, such as the oxidation of Cr(III) to Cr(VI) by manganese oxides in chromium-rich soils, minerals and sediments under natural conditions. This process may cause an increase in the concentration of Cr(VI). The other is anthropogenic sources, which are the main source of Cr(VI) pollution in the environment and come in various forms. From the mining, beneficiation and smelting of chromium-containing ores, the production of chromium chemicals, and industrial production applications such as electroplating and leather tanning, a large amount of chromium-containing wastewater and wastes are improperly disposed of or leaked into natural water bodies and soil environments due to emergency accidents.

[0004] Therefore, providing an anion exchange resin for removing dichromate ions in aqueous solution and a preparation method thereof is a problem to be solved by those skilled in the art. Summary of the invention

[0005] In view of this, the present invention provides an anion exchange resin for removing dichromate ions in an aqueous solution, and a preparation method and application thereof.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] An anion exchange resin comprises: a synthetic monomer, an initiator and a cross-linking agent;

[0008] Wherein, the synthetic monomers include: acrylamide and methacryloyloxyethyl trimethyl ammonium chloride.

[0009] Preferably, the mass ratio of the methacryloyloxyethyltrimethylammonium chloride to the acrylamide is 7:3.

[0010] Preferably, the initiator comprises: potassium persulfate;

[0011] The mass ratio of the potassium persulfate to the acrylamide is 1:20.

[0012] Preferably, the cross-linking agent includes: N,N-methylenebisacrylamide;

[0013] The mass ratio of the N,N-methylenebisacrylamide to the acrylamide is 1:20.

[0014] The anion exchange resin for removing dichromate in aqueous solution prepared by the invention has a fast removal rate and can be reused.

[0015] When the pH value of the aqueous solution is 4.78 and the dichromate ion content of the aqueous solution is 200 mg / L, 150 mg of anion exchange resin is added to 50 ml of the aqueous solution and shaken in a constant temperature incubation shaker at 25°C and 160 rpm for 1 hour, the dichromate removal rate in the aqueous solution can reach 94.21%; the resin can be regenerated by analysis with 1 mol / L HCl solution, and after 4 cycles of adsorption-regeneration, the performance of the resin in adsorbing dichromate only decreases by 6.32%.

[0016] In addition, the anion exchange resin has a strong compressive strength of 90.23 KPa. After separating and adsorbing dichromate ions from an aqueous solution, the resin will not break due to insufficient compressive strength.

[0017] The above-mentioned method for preparing an anion exchange resin comprises the following specific steps:

[0018] (1) Weigh acrylamide, methacryloyloxyethyl trimethyl ammonium chloride, potassium persulfate and N,N-methylenebisacrylamide according to weight ratio;

[0019] (2) dissolving acrylamide and methacryloyloxyethyl trimethyl ammonium chloride in deionized water, heating and stirring to obtain a synthetic monomer solution;

[0020] (3) dissolving potassium persulfate in deionized water to obtain a potassium persulfate solution for later use;

[0021] (4) dissolving N,N-methylenebisacrylamide in ionized water to obtain an N,N-methylenebisacrylamide solution for later use;

[0022] (5) adding the potassium persulfate solution and N,N-methylenebisacrylamide solution to the synthetic monomer solution in sequence, and continuing heating and stirring to obtain a mixed solution;

[0023] (6) When the mixed solution solidifies, stop stirring and continue heating to obtain a solid resin;

[0024] (7) The solid resin described in step (6) is shredded and dried, and the dry resin after being shredded by a crusher is the anion exchange resin.

[0025] Preferably, the heating temperature in step (2) is 70° C., and the mixture is stirred until the temperature of the synthetic monomer solution reaches 70° C.;

[0026] The weight of the deionized water in step (2) is 1.5 times the total weight of acrylamide and methacryloyloxyethyltrimethylammonium chloride.

[0027] Preferably, the weight of the deionized water in step (3) is 0.5 times the total weight of acrylamide and methacryloyloxyethyltrimethylammonium chloride;

[0028] The weight of the deionized water in step (4) is 1 times the total weight of acrylamide and methacryloyloxyethyltrimethylammonium chloride.

[0029] Preferably, the heating temperature in step (5) is 70° C.

[0030] The heating temperature in step (6) is 70° C. and the heating time is 3 hours.

[0031] Preferably, the particle size of the anion exchange resin after crushing in step (7) is 0.45-1 mm;

[0032] The drying condition in step (7) is 70° C. in an electric blast drying oven;

[0033] The drying time in step (7) is 12 hours.

[0034] Another object of the present invention is to provide the use of the above-mentioned anion exchange resin in removing dichromate ions in aqueous solution.

[0035] Preferably, the anion exchange resin has a removal effect on dichromate ions in the pH range of 2-10, and the pH with the best removal rate is 4.78.

[0036] Preferably, the method of use is: immersing the anion exchange resin in a dichromate solution, and after adsorption is completed, separating the aqueous solution from the anion exchange resin with a filter.

[0037] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0038] The present invention introduces methacryloyloxyethyl trimethyl ammonium chloride into the polyacrylamide resin polymerization system, so that the water-absorbing resin has a quaternary ammonium salt -N(CH3)3 + The functional group can realize the removal of dichromate ions from aqueous solution; in addition, due to the unique characteristics of acrylamide during resin synthesis, the compressive strength of the resin is enhanced, and the resin will not break after being separated from the aqueous solution after adsorbing dichromate ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0040] Figure 1 This is a scanning electron microscope image of the anion exchange resin prepared in Example 1 of the present invention;

[0041] Figure 2 The anion exchange resin of the present invention is used to treat Cr2O7 2- Adsorption effect diagram;

[0042] Figure 3 AM:DMC ratio to Cr2O7 2- Effect diagram of removal rate;

[0043] Figure 4 The dosage of MBA on Cr2O7 2- Effect diagram of removal rate;

[0044] Figure 5 KPS dosage for Cr2O7 2- Effect diagram of removal rate. DETAILED DESCRIPTION

[0045] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0046] Example 1

[0047] A method for preparing an anion exchange resin for removing dichromate ions in an aqueous solution, specifically comprising the following steps:

[0048] (1) Weigh 3 g acrylamide and 7 g methacryloyloxyethyl trimethyl ammonium chloride and dissolve them in 15 ml deionized water. Weigh 0.15 g potassium persulfate and dissolve it in 5 ml deionized water. Weigh 0.15 g N,N-methylenebisacrylamide and dissolve it in 10 ml deionized water.

[0049] (2) placing acrylamide and methacryloyloxyethyl trimethyl ammonium chloride solution in a 70° C. water bath and heating until the temperature of the acrylamide and methacryloyloxyethyl trimethyl ammonium chloride solution reaches 70° C., and turning on magnetic stirring during the heating to mix acrylamide and methacryloyloxyethyl trimethyl ammonium chloride evenly.

[0050] (3) The potassium persulfate solution and the N,N-methylenebisacrylamide solution were sequentially added to the acrylamide and methacryloyloxyethyltrimethylammonium chloride solution, and the stirring was stopped after the solution solidified, and the solution was heated at 70° C. for 3 hours.

[0051] (4) Cut the solid resin into pieces and dry them in an electric blast drying oven at 70° C. for 12 hours. Use a crusher to crush the dried resin. The resin particles with a particle size of 0.45-1 mm are the anion exchange resin used to remove dichromate ions in aqueous solution.

[0052] Application Example 1

[0053] Prepare 200mg / L Cr2O7 2- Solution, take 50mlCr2O7 2- The solution was transferred into a conical flask. Accurately weigh 150 mg of anion exchange resin and place it in a flask containing Cr2O7 2- In a conical flask containing the solution, mix the anion exchange resin and Cr2O7 2- The conical flask of the solution was placed in a constant temperature incubator shaker, the temperature was set at 25°C, the shaking speed was 160 rpm, and the shaking time was 1 hour.

[0054] After the reaction is completed, the anion exchange resin is filtered out and the Cr2O7 2- The solution was tested. After one hour of reaction, Cr2O7 2- Cr2O7 in solution 2- The concentration dropped by 94.21%.

[0055] Effect experiment

[0056] AM (acrylamide): DMC (methacryloyloxyethyl trimethyl ammonium chloride) ratio influence

[0057] See also Figure 3 When the mass ratio of AM:DMC is 0:10, 1:9, 2:8, 3:7, 4:6, 5:5 and 10:0, the removal rates are 91.95%, 93.82%, 91.06%, 87.65%, 79.83%, 71.11% and 0%, respectively. It can be seen that the maximum removal rate is obtained when the ratio is 1:9. As the amount of DMC is gradually reduced, the removal rate gradually decreases. This may be due to the fact that as the amount of DMC decreases, the active functional group quaternary ammonium salt -N(CH3)3 +The amount decreases, resulting in a decrease in removal efficiency.

[0058] Changing the amount of AM added will affect the overall mechanical strength of the gel. The mechanical strengths when the AM:DMC mass ratios are 0:10, 1:9, 2:8, 3:7, 4:6, 5:5 and 10:0 are 14.00, 47.83, 58.14, 104.50, 96.59, 110.99 and 497.40 KPa, respectively. As the amount of AM added increases, the overall mechanical strength shows an increasing trend.

[0059] In summary, gel needs to have high Cr2O7 2- The removal rate and excellent mechanical strength facilitate the preparation and application of the gel, so the mass ratio of AM:DMC is 3:7 as the optimal ratio. 2- The removal rate is 87.65% and the mechanical strength is 104.50KPa.

[0060] Effect of MBA (N,N-methylenebisacrylamide) dosage

[0061] See also Figure 4 Under the condition of the optimal mass ratio of AM:DMC being 3:7, when the amount of crosslinking agent MBA was 0.05, 0.10, 0.15, 0.20, 0.3 g, Cr2O7 2- The removal rates were 80.02%, 80.78%, 85.16%, 85.22% and 85.87% respectively, and the mechanical strengths were 41.82, 81.07, 78.44, 72.46 and 83.35 KPa respectively. The mechanical strength fluctuated in a small range after 0.10 g, and the removal rate did not change significantly after 0.15 g. In summary, 0.15 g was selected as the amount of crosslinking agent added for PAD resin synthesis.

[0062] Optimization of initiator KPS dosage

[0063] When the mass ratio of AM:DMC is optimal at 3:7 and the amount of crosslinker MBA is 0.15g, the amount of initiator KPS is 0.05, 0.10, 0.15, 0.20, 0.3g. 2-The removal rates were 83.48%, 83.79%, 83.73%, 83.11% and 81.75%, respectively, and the mechanical strengths were 53.09, 77.68, 90.23, 78.21 and 66.45 KPa, respectively. When the initiator dosage increased from 0.05g to 0.15g, the mechanical strength continued to increase, and when the initiator dosage increased from 0.15g to 0.3g, the mechanical strength gradually decreased. The possible reason is that the free radicals generated before reaching the maximum mechanical strength are not enough to satisfy all unsaturated C=C double bonds to open to form chain and network structures, and with the increase in dosage, the number of free radicals generated reaches saturation, and the excess free radicals attack the polymerized chain or network structure, breaking the chemical bonds, thereby reducing the mechanical strength of the gel. Therefore, 0.15g of initiator KPS dosage is selected as the optimal ratio.

[0064] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.

[0065] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An anion exchange resin, characterized in that include: Synthetic monomers, initiators and crosslinking agents; wherein the synthetic monomers include acrylamide and methacryloyloxyethyl trimethylammonium chloride.

2. An anion exchange resin according to claim 1, characterized in that: The mass ratio of the methacryloyloxyethyltrimethylammonium chloride to the acrylamide is 7:

3.

3. An anion exchange resin according to claim 2, characterized in that: The initiator includes: potassium persulfate; The mass ratio of the potassium persulfate to the acrylamide is 1:

20.

4. An anion exchange resin according to claim 3, characterized in that: The cross-linking agent includes: N,N-methylenebisacrylamide; The mass ratio of the N,N-methylenebisacrylamide to the acrylamide is 1:

20.

5. A method for preparing an anion exchange resin as claimed in claim 4, characterized in that: The specific steps include: (1) Weigh acrylamide, methacryloyloxyethyl trimethyl ammonium chloride, potassium persulfate and N,N-methylenebisacrylamide according to weight ratio; (2) dissolving acrylamide and methacryloyloxyethyl trimethyl ammonium chloride in deionized water, heating and stirring to obtain a synthetic monomer solution; (3) dissolving potassium persulfate in deionized water to obtain a potassium persulfate solution for later use; (4) dissolving N,N-methylenebisacrylamide in ionized water to obtain an N,N-methylenebisacrylamide solution for later use; (5) adding the potassium persulfate solution and N,N-methylenebisacrylamide solution to the synthetic monomer solution in sequence, and continuing heating and stirring to obtain a mixed solution; (6) When the mixed solution solidifies, stop stirring and continue heating to obtain a solid resin; (7) The solid resin described in step (6) is shredded and dried, and the dry resin after being shredded by a crusher is the anion exchange resin.

6. The method for preparing an anion exchange resin according to claim 5, characterized in that: The heating temperature in step (2) is 70° C., and the mixture is stirred until the temperature of the synthetic monomer solution reaches 70° C.; The weight of the deionized water in step (2) is 1.5 times the total weight of acrylamide and methacryloyloxyethyltrimethylammonium chloride.

7. The method for preparing an anion exchange resin according to claim 5, characterized in that: The weight of the deionized water in step (3) is 0.5 times the total weight of acrylamide and methacryloyloxyethyl trimethylammonium chloride; The weight of the deionized water in step (4) is 1 times the total weight of acrylamide and methacryloyloxyethyltrimethylammonium chloride.

8. The method for preparing an anion exchange resin according to claim 5, characterized in that: The heating temperature in step (5) is 70° C. The heating temperature in step (6) is 70° C. and the heating time is 3 hours.

9. The method for preparing an anion exchange resin according to claim 5, characterized in that: The particle size of the anion exchange resin after crushing in step (7) is 0.45-1 mm; The drying condition in step (7) is 70° C. in an electric blast drying oven; The drying time in step (7) is 12 hours.

10. Use of the anion exchange resin according to any one of claims 1 to 4 or the anion exchange resin prepared by the preparation method according to any one of claims 5 to 9 in removing dichromate ions from an aqueous solution.

Citation Information

Patent Citations

  • Weakly alkaline gel ion exchange resin for adsorbing hexavalent chromium and preparation method of weakly alkaline gel ion exchange resin

    CN117003939A

  • Method of recovering phosphorous in water

    JP2024087945A

Cited By

  • Preparation method of polyquaternium functionalized non-woven fabric

    CN121675226A